FAKTOR PENENTU KEPUTUSAN PEMBELIAN PADA PRODUK PRIVATE LABEL DI INDOMARET FRESH SPBU SULTAN AGUNG KEDATON BANDAR LAMPUNG - Muhammad Zaini Saputra; Driya Wiryawan; Mudji Rachmat Ramelan (Nusantara Hasana Journal, 2026)
Private label products have become an alternative offered by modern retailers because they are relatively more affordable while maintaining quality that can compete with national branded products. Consumers' purchasing decisions regarding private label products are influenced by several factors, including Advertising, Distribution Intensity, Price, Store Image, and Store Location. Therefore, this study aims to analyze the influence of these five variables on purchasing decisions for private label products at Indomaret Fresh SPBU Sultan Agung Kedaton Bandar Lampung. This study employed a quantitative approach using a survey method. The research sample consisted of 100 respondents who were consumers of private label products at Indomaret Fresh SPBU Sultan Agung Kedaton Bandar Lampung. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results indicate that Advertising, Distribution Intensity, Price, Store Image, and Store Location have a positive and significant effect on purchasing decisions for private label products. Among these variables, Price was found to be the most dominant factor influencing consumers’ purchasing decisions. These findings suggest that improving advertising quality, ensuring product availability, setting appropriate prices, maintaining a positive store image, and selecting a strategic store location can significantly enhance consumers’ purchasing decisions toward private label products.